Analisis Return On Investment (ROI) Dan Residual Income (RI) Untuk Menilai Kinerja Keuangan Pada PT. Industri Jamu Dan Farmasi Sido Muncul, Tbk Yang Terdaftar Di BEI Periode 2018-2022 - Delsiana Yestin; Imanuel Wellem; Paulus Juru (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
This research aimed to determine the financial performance of PT Herbal Medicine and Pharmaceutical Industry Sido Muncul, Tbk used Return On Investment (ROI) and Residual Income (RI) analysis. The sample in this research was the financial statements of PT. Herbal Medicine and Pharmaceutical Industry Sido Muncul Tbk from 2018-2022. The type of data used was secondary data Data collection was carried out using the documentation method, the data sources used were taken from the official website of the Indonesia Stock Exchange. The research showed that the financial performance of PT. The Sido Muncul Herbal Medicine and Pharmaceutical Industry for the 2018-2022 time frame used Return On Investment (ROI) analysis to assess the financial performance of PT. The Sido Muncul Herbal Medicine and Pharmaceutical Industry were in good condition by producing positive ROI, but its state was still erratic. Based on industry standards, the company's ability to return on investment was good, which means that the company's financial performance has been effective. However, according to the Residual Income (RI) calculation, in assessing the financial performance of the financial company PT. The Sido Muncul Herbal and Pharmaceutical Industry revealed that the RI obtained had a negative value for 5 consecutive years during the 2018-2022 period due to the cost of the company's capital. Thus, it can be said that the company has not been able to provide economic added value for shareholders and that its financial performance has not been effective and efficient because the R1>0.